Mainstreaming access and benefit sharing in agricultural Research and Development: a workshop for researchers, practitioners and policy makers in selected African countries and organizations - López Noriega, Isabel; Tiambo, Christian (2022)
The workshop Mainstreaming access and benefit sharing in agricultural Research and Development: a workshop for researchers, practitioners and policy makers in selected African countries and organizations was held at the International Livestock Research Institute (ILRI) in Addis Ababa from the 21st to the 24th of November 2022. The workshop was co-organized by the African Union Commission, ILRI and the CGIAR Genebank Initiative, and funded by the CGIAR Genebank Initiative. It brought together about 35 participants from national and international research organizations, regional and continental intergovernmental organizations, national ministries of environment and agriculture, private sector and farmers’ associations. The list of participants can be found in Annex 1 of this report. The objectives of the workshop were: • Raise awareness about the role of ABS in reaching pan-African objectives of sustainable agricultural development, food security and climate change adaptation. • Facilitate exchange of experiences in implementing ABS systems • Raise the profile of ABS procedures for reaching development objetives • Identify examples of how organizations have mainstreamed compliance with national ABS measures • Identify challenges for parties and brainstorm on potential solutions. • Exchange views on ABS for digital sequence information (DSI), taking into account practitioners’ actual use of DSI and ongoing international level consideration of the issue. • Initiate or strengthen dialogue between practitioners and national policy makers about guiding principles for mainstreaming ABS in agricultural research and development, • Advance the development of AUC template for material transfer agreement. • Advance on the consideration of ABS issues within concrete initiatives, including the Consortium Agreement on genomic reference resource for African cattle and the African Network of Animal Germplasm Biobanks The workshop agenda included the main following topics: - Setting the scene on ABS in Africa - ABS in agricultural research and development projects - Guiding principles for mainstreaming ABS in agricultural research and development - The African Union Commission template of Material Transfer Agreement